2022
DOI: 10.3389/fimmu.2022.1022228
|View full text |Cite
|
Sign up to set email alerts
|

The role of PD-1/PD-L1 axis in idiopathic pulmonary fibrosis: Friend or foe?

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating interstitial lung disease with a bleak prognosis. Mounting evidence suggests that IPF shares bio-molecular similarities with lung cancer. Given the deep understanding of the programmed cell death-1 (PD-1)/programmed death-ligand 1 (PD-L1) pathway in cancer immunity and the successful application of immune checkpoint inhibitors (ICIs) in lung cancer, recent studies have noticed the role of the PD-1/PD-L1 axis in IPF. However, the conclusions are ambiguous, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 165 publications
0
5
0
Order By: Relevance
“…Currently, the most common approach to replicate the pathological process of human IPF in C57BL/6 mice involves intratracheal injection of the cytotoxic drug bleomycin. 44,45 In our study, 5 mg/kg of bleomycin or an equal amount of PBS was intranasally introduced to male C57BL/6 mice three times. Subsequently, after 5 days of bleomycin or PBS injection, 1 × 10 6 LLC cells were intravenously inoculated into the mice to establish the orthotopic murine model of LUAD with coexistent IPF (LC-PF) or without (LC).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the most common approach to replicate the pathological process of human IPF in C57BL/6 mice involves intratracheal injection of the cytotoxic drug bleomycin. 44,45 In our study, 5 mg/kg of bleomycin or an equal amount of PBS was intranasally introduced to male C57BL/6 mice three times. Subsequently, after 5 days of bleomycin or PBS injection, 1 × 10 6 LLC cells were intravenously inoculated into the mice to establish the orthotopic murine model of LUAD with coexistent IPF (LC-PF) or without (LC).…”
Section: Methodsmentioning
confidence: 99%
“…These investigators also reported that the expression of PD-L1 was clearly increased in the lungs of patients with idiopathic pulmonary fibrosis (IPF). It is known that the PD-1/PD-L1 signaling pathway has a crucial profibrotic role in the development of IPF disease [ 22 , 47 ], although it is not known whether it is caused by intrinsic or extrinsic regulation. Interestingly, Gao et al [ 48 ] demonstrated that the acetylation of the PD-L1 protein at Lys263 within its cytoplasmic tail regulated the translocation of the PD-L1 protein from the cell-surface into the nucleus.…”
Section: The Immunosuppressive Pd-1/pd-l1 Checkpoint Pathwaymentioning
confidence: 99%
“…The differentiation of tissue fibroblasts into fibrogenic myofibroblasts and an increase in the numbers of senescent fibroblasts are the major hallmarks of fibrotic lesions [ 75 , 80 ]. Emerging studies have revealed that the function of the PD-1/PD-L1 axis has a crucial role in the accumulation of fibrotic lesions [ 22 , 47 ]. There are a number of investigations indicating that in mouse and human fibrotic tissues, there exists a robust increase in the expression of PD-L1 protein not only in fibroblasts but also in endothelial and epithelial cells [ 18 , 22 , 44 , 47 , 81 ].…”
Section: Pd-1/pd-l1 Signaling Is Augmented In Many Age-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging literature highlights the potential of PDL1 inhibition in reducing fibrosis severity in pulmonary fibrosis, and the PDL1 pathway mainly plays a role in promoting fibrosis rather than its immunomodulatory role ( 84 ). The fibrotic effect of PDL1 in IPF arises from intricate cellular interactions and signaling pathways, with the following mechanisms assuming paramount significance( Figure 4 ): firstly, overexpression of PDL1 in lung fibroblasts exerts resistance to myoblast apoptosis and eludes macrophage phagocytosis via the inhibition of p53 pathway or activation of FAK pathway.…”
Section: The Multifunctional Role Of Pdl1 In Emt: From Immune Evasion...mentioning
confidence: 99%